2013
DOI: 10.3758/s13415-013-0153-y
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguous emotion recognition in temporal lobe epilepsy: The role of expression intensity

Abstract: The nal publication is available at Springer via https://doi.org/10.3758/s13415-013-0153-y Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 63 publications
(113 reference statements)
1
33
1
Order By: Relevance
“…A larger sample would be necessary to test for laterality effects in patients with insular damage more specifically, but these data suggest that the left insular injury may be associated with more severe impairments in social information processing. These results are discordant with the right-hemisphere hypothesis of emotion processing (Sedda et al, 2013;Yuvaraj et al, 2013), and with the results from a lesionmapping study involving over 100 patients, which showed that lesions in the right somatosensory-related cortices, including the insula, were associated with impaired recognition of emotions from human facial expressions (Adolphs et al, 2000). Nevertheless, a more recent, large voxel-based lesion-symptom mapping found that only the left insula was significantly involved in facial emotion recognition impairment following penetrating brain injury (Dal Monte et al, 2013).…”
Section: Discussioncontrasting
confidence: 47%
“…A larger sample would be necessary to test for laterality effects in patients with insular damage more specifically, but these data suggest that the left insular injury may be associated with more severe impairments in social information processing. These results are discordant with the right-hemisphere hypothesis of emotion processing (Sedda et al, 2013;Yuvaraj et al, 2013), and with the results from a lesionmapping study involving over 100 patients, which showed that lesions in the right somatosensory-related cortices, including the insula, were associated with impaired recognition of emotions from human facial expressions (Adolphs et al, 2000). Nevertheless, a more recent, large voxel-based lesion-symptom mapping found that only the left insula was significantly involved in facial emotion recognition impairment following penetrating brain injury (Dal Monte et al, 2013).…”
Section: Discussioncontrasting
confidence: 47%
“…The most commonly used face stimulus series were static black and white images from Ekman and Friesen (1976). In some studies 60 pictures were used (Calder et al, 1996;Reynders et al, 2005;Walpole et al, 2008;Sedda et al, 2013;Wendling et al, 2015), with 10 stimuli for each basic emotion (happiness, fear, anger, sadness, disgust, surprise). In other studies 24-42 facial expressions were used (Adolphs et al, 1995(Adolphs et al, , 2001Young et al, 1996;Anderson et al, 2000;Meletti et al, 2003aMeletti et al, ,b, 2009Benuzzi et al, 2004;Yamada et al, 2005;Shaw et al, 2007;Bonora et al, 2011), typically with four-five stimuli for each emotion.…”
Section: Studies Of Facial Emotion Recognitionmentioning
confidence: 99%
“…In patient only studies, [22] reported that patients who scored high for psychopathy were found to have impaired recognition of sadness at low intensity compared to those with low psychopathy, whilst [59] found that violent schizophrenia patients were less able to assess the intensity of emotions than non-violent patients. As such, research investigating emotion intensity using static stimuli suggests that the intensity at which an emotion is expressed may influence a patient's ability to correctly identify that emotion [57].…”
Section: Introductionmentioning
confidence: 99%